HUBUNGAN ANTARA SIKAP TERHADAP PENERAPAN PROGRAM K3 DENGAN KOMITMEN KARYAWAN PADA PERUSAHAAN - B, Yenny Oktorita; Rosyid, Haryanto F; Lestari, Anita (Jurnal Psikologi, 2001)
This study aims to reveal relationship between employee’s attitudes toward occupational safety and health programs, and organizational commitment. A lot of studies found that organizational commitment closely related to the attitudes of employees toward the administration of occupational safety and health program in organization. Two measures are developed to investigate the two variables, i.e.: one instruments is designed to measure employees’ attitudes and the other for measuring organizational commitment. The subjects are employees of the portland cement factory in West Java, consists of 100 people of staff and non staff worker. The result shows significant correlation between attitudes toward administration of occupational safety and health programs, and employees’ organizational commitment (r= 0,381; p< 0,01)